The Influence of Project-Based Learning Models on Critical Thinking Ability and Basic Science Learning Outcomes - Raysyah Putri Sitanggang; Haryanto Haryanto (Proceedings Series on Social Sciences & Humanities, 2023)
The main objective of this study was to analyze: (1) better influence the outcomes of learning science students taught by Projek Based Learning learning model and model of Direct Instruction; and (2) better effect between critical thinking skills that are taught by Projek Based Learning learning model and model of Direct Instruction. This research is a quasi-experiment conducted in SD Negeri 064973 Medan. The population in this study were all 50 students of class VII, while the sample in this study were students of class VI-A total of 25 people with learning models Projek Based Learning, and students of class VI-B as many as 25 people with Direct Instruction models. The instrument used consisted of test learning outcomes to shape totaled 9 points and can test the reliability of 0,374 and totaled 18 items critical points and has a reliability of 0.831. Data analysis was performed using independent samples test t-aided assisted software SPSS 16.0 for windows. The result showed that: (1) the effect of the Project the based Learning learning model is better than the direct instruction model to learn science students' outcomes. It is based on the acquisition tcount of 2,892 scores greater than ttable of 2.060 and (2) the effect of the Project Based Learning learning model is better compared with the direct instruction learning model t the student's critical thinking skills. It is based on the acquisition score tcount of 2,944 greater than ttable of 2.060.